2019
DOI: 10.20517/2574-1225.2018.69
|View full text |Cite
|
Sign up to set email alerts
|

Intracorporeal hemi-hand-sewn technique for Billroth-I gastroduodenostomy after laparoscopic distal gastrectomy: comparative analysis with laparoscopy-assisted distal gastrectomy

Abstract: How to cite this article: Ohmura Y, Suzuki H, Kotani K, Teramoto A. Intracorporeal hemi-hand-sewn technique for Billroth-I gastroduodenostomy after laparoscopic distal gastrectomy: comparative analysis with laparoscopy-assisted distal gastrectomy.Mini-invasive Surg 2019;3:4. http://dx. AbstractAim: The purpose of this study was to evaluate the clinical feasibility and efficacy of the intracorporeal hemi-hand-sewn (IC-HHS) technique for Billroth-I gastroduodenostomy in comparison with extracorporeal total hand-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…More and more GI reconstruction can be performed intracorporeally especially in LDG. Ohmura et al [7] reported a new reconstruction method named hemi-hand-sewn (HHS) technique. The HHS technique combines linear stapler in posterior wall with hand sewn in anterior wall to create Billroth-I anastomosis.…”
mentioning
confidence: 99%
“…More and more GI reconstruction can be performed intracorporeally especially in LDG. Ohmura et al [7] reported a new reconstruction method named hemi-hand-sewn (HHS) technique. The HHS technique combines linear stapler in posterior wall with hand sewn in anterior wall to create Billroth-I anastomosis.…”
mentioning
confidence: 99%